ENTRE AS PRÁTICAS DAS TEORIAS E VICE-VERSA - A PRÁTICA DE ENSINO COMO COMPONENTE CURRICULAR NAS LICENCIATURAS EM HISTÓRIA NO BRASIL APÓS 2002 - Ferreira, Angela Ribeiro (2015)
The "practice as a curricular component" in the training of history teachers in Brazil is the object of this thesis. The data used are the Pedagogical Projects in History Course Degree of federal and state Brazilian universities and the testimony of history teachers trainers involved in the curriculum change in their courses and / or implementation of new curriculum. The analysis is done from the perspective of comparative education with the support of content analysis. The general objective was to analyze comparatively the impact of the mandatory of practicing as a curricular component in undergraduate courses of History in Brazil. To do so, we sought to: identify and compare the design of degree, the conceptions of history and history teaching, curriculum concepts that guide the pedagogical projects; check for peculiarities in interpretation of the law of teaching practice expanding; discern which guidelines have most influenced the definition of the curriculum of each course if it has been The National Guidelines of History or the Teacher Training Guidelines. Data analysis involved discussions on curriculum from the perspective of the critical theory, theory and practice relation, and formation of history teachers, history teaching and comparative education. In the analysis of the sources we have found courses organized mostly within the quadripartite model of General History (Ancient, Medieval, Modern and Contemporary History), courses focused on the social function of historical knowledge and the indivisibility between teaching and research. We identified different models of organization for the 400 hours of teaching practice. We call it model of Specialized Responsibility when the practice occurs in the form of specific disciplines of history teaching with different denominations and summaries. The Model of Shared Responsibility describes the 400 hours of practice diluted across the curriculum framework or just across the historical content disciplines. The model of non-responsibility of the historian with the teaching designates the allocation of educational and historical research disciplines as practice workload, denying specificity to curricular component. In the first model, the summaries are very varied handling many possible topics for the history teaching: what to teach, how to teach, knowledge production, official documents, teaching materials, teaching profession, media and teaching history. In the interviews it was possible to identify historical and political factors prior to reformulations, as well as internal disputes and negotiated consensus in the production of curriculum and the difficulties in the implementation of Practice as a Curricular Component. Among the difficulties are the lack of trained professors graduated in area of teaching, non-recognition of teaching history as part of the history field, devaluation of the teaching area within the course, the non-participation of the teaching area professors in the process of definition of the curriculum .